Moda e co-branding: uma associação de sucesso (ModaPalavra e-periódico, 2010)
The association between brands of Fashion, and other distinct segments, has been an increasingly habitual action in the business world, exemplified by several cases of success. This means that the partnership between the brands, or co-branding, is a strategy that can benefit them. The term may be defined as the combination of two or more marks in the same of er, double value, where it is expected that the status of a brand is reflected in the other. The companies of fashion that have the complex task of translating, in products, desires, lifestyle and personality of the target audience, and the desire for renewal and the new, benefit from this action is seeking to include in their products, intangible and subjective values that are the dif erence in the competitive market today.
Keywords: Co-branding; Brands; Fashion